The use of the Nursing Activities Score in clinical settings: an integrative review - Joanie Lachance; Frédéric Douville; Clémence Dallaire; Katia Grillo Padilha; Maria Cecilia Gallani (SciELO, 2015)
ABSTRACT Objective analyze how studies have approached the results obtained from the application of the Nursing Activities Score (NAS) based on Donabedian's model of healthcare organization and delivery. Method CINAHL and PubMed databases were searched for papers published between 2003 and March 2015. Results 36 articles that met the inclusion criteria were reviewed and double-coded by three independent coders and analyzed based on the three elements of Donabedian's health care quality framework: structure, process and outcome. The most frequently addressed, but not always tested, variables were those that fell into the structure category. Conclusion variables that fell into the process category were used less frequently. Beside NAS, the most frequently used variables in the outcome category were mortality and length of stay. However, no study used a quality framework for healthcare or NAS to evaluate costs, and it is recommended that further research should explore this approach.